2016
DOI: 10.1590/s1518-8787.2016050006465
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and potential years of life lost by road traffic injuries in Brazil, 2013

Abstract: OBJECTIVE To estimate the potential years of life lost by road traffic injuries three years after the beginning of the Decade of Action for Traffic Safety.METHODS We analyzed the data of the Sistema de Informações sobre Mortalidade (SIM – Mortality Information System) related to road traffic injuries, in 2013. We estimated the crude and standardized mortality rates for Brazil and geographic regions. We calculated, for the Country, the proportional mortality according to age groups, education level, race/skin c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
18
0
18

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 16 publications
4
18
0
18
Order By: Relevance
“…In the end of the analysis period (2008), the rates were similar (4.7/100 thousand people) to the mortality rates of pedestrians (5.4/100 thousand people). Andrade and Mello-Jorge 6 found that the mortality rates per 100 thousand residents, from 2011 on, among motorcycle riders had already overcome those of pedestrians and automobile occupants, which remained unchanged in 2012 and 2013. This discrepancy in the mortality rates of motorcycle riders, pedestrians, and automobile occupants, if we compare GBD data with those from the SIM, can be due to the process of death codes redistribution and adjustments of garbage codes used in the GBD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the end of the analysis period (2008), the rates were similar (4.7/100 thousand people) to the mortality rates of pedestrians (5.4/100 thousand people). Andrade and Mello-Jorge 6 found that the mortality rates per 100 thousand residents, from 2011 on, among motorcycle riders had already overcome those of pedestrians and automobile occupants, which remained unchanged in 2012 and 2013. This discrepancy in the mortality rates of motorcycle riders, pedestrians, and automobile occupants, if we compare GBD data with those from the SIM, can be due to the process of death codes redistribution and adjustments of garbage codes used in the GBD.…”
Section: Discussionmentioning
confidence: 99%
“…There has been a decrease of pedestrian deaths since 2007 5 . In 2013, there were 42,266 deaths with a mortality rate of 21/100 thousand people and 1.3 million of potential years of life lost due to injuries in younger age ranges 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Rates in the other macroregions were 69.4 (North), 69.8 (South), and 88.6 (Southeast) per 100,000 inhabitants [3]. A study using data from the Mortality Information System found that in 2013 RTIs-related mortality rates in each macroregion were 30.0 (Central-West), 23.5 (Northeast), 23.4 (South), 22.4 (North), and 26.8 (Southeast) per 100,000 [4]. In this study, the prevalence of self-reported RTIs within the previous 12 months was lowest in the Southeast (5.1%; 95.0% CI: 3.9-6.6) and South (5.6%; 95.0% CI: 4.2-7.6) macroregions, and higher in the Central-West (7.4%; 95.0% CI: 5.5-9.9), Northeast (8.2%; 95.0% CI, 6.5-10.1), and North (11.2%; 95.0% CI: 8.4-14.8) (data not shown in tables).…”
Section: Discussionmentioning
confidence: 99%
“…In 2013, RTIs were the cause of 170,805 admissions to the Brazilian public health system (Sistema Único de Saúde-in Portuguese), a rate of 85 admissions per 100,000 inhabitants, with the highest rates found in the Central-West and Northeast macroregions [3]. A mortality rate by RTIs of 21 deaths per 100,000 inhabitants was observed in Brazil in 2013, with the highest rate found in the Central-West macroregion [4]. Estimates show that RTIs-related deaths can result in costs of up to 6% of gross domestic product (GDP) [5].…”
Section: Introductionmentioning
confidence: 99%
“…Isso resulta em elevados encargos aos sistemas previdenciário e de saúde, constituindo a principal causa de anos potenciais de vida perdidos por acidentes e violências. Beber em binge determina maior gravidade das lesões e fatalidade dos acidentes (3,18) .…”
Section: Discussionunclassified